2022
DOI: 10.1097/cji.0000000000000442
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antacid Use on Immune Checkpoint Inhibitors in Advanced Solid Cancer Patients: A Systematic Review and Meta-analysis

Abstract: The influence of antacids use on immune checkpoint inhibitor (ICI) efficacy remains unclear. A systematic review and meta-analysis was performed to evaluate the effect of proton pump inhibitors (PPIs) and histamine-2-receptor antagonists (H2RAs) on ICI efficacy in advanced solid cancer patients. A systematic literature search in PubMed, EMBASE, and Web of Science was performed to retrieve studies investigating the effect of antacid use on ICI efficacy. Overall survival (OS), progressionfree survival (PFS), obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 126 publications
1
0
0
Order By: Relevance
“…These results were in good agreement with the meta-analysis of Deng et al. (n = 16,147 patients, 30 publications) ( 57 ) and Chen et al. (n = 15,957 patients, 33 studies) ( 58 ).…”
Section: Discussionsupporting
confidence: 91%
“…These results were in good agreement with the meta-analysis of Deng et al. (n = 16,147 patients, 30 publications) ( 57 ) and Chen et al. (n = 15,957 patients, 33 studies) ( 58 ).…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, this study revealed no significant difference in the occurrence of adverse reactions during the course of ICI combined therapy between the PPI and non-PPI groups, consistent with the findings of several other studies. 28–30 However, other studies have reported an association between the use of PPIs and an increased incidence of adverse reactions related to ICIs. 11 , 31 The relationship between PPIs and the occurrence of immune-related adverse events in patients remains inconclusive.…”
Section: Discussionmentioning
confidence: 97%